Slow acidification of the winter mixed layer in the subarctic western North Pacific. Issue 8 (30th August 2017) - Wakita, Masahide; Nagano, Akira; Fujiki, Tetsuichi; Watanabe, Shuichi
Abstract: We used carbon dioxide (CO2 ) system data collected during 1999–2015 to investigate ocean acidification at time series sites in the western subarctic region of the North Pacific Ocean. The annual mean pH at station K2 decreased at a rate of 0.0025 ± 0.0010 year −1 mostly in response to oceanic uptake of anthropogenic CO2 . The Revelle factor increased rapidly (0.046 ± 0.022 year −1 ), an indication that the buffering capacity of this region of the ocean has declined faster than at other time series sites. In the western subarctic region, the pH during the winter decline at a slower rate of 0.0008 ± 0.0004 year −1 . This was attributed to a reduced rate of increase of dissolved inorganic carbon (DIC) and an increase of total alkalinity (TA). The reduction of DIC increase was caused by the decline of surface water density associated with the pycnocline depression and the reduction of vertical diffusion flux from the upper pycnocline. These physical changes were probably caused by northward shrinkage of the western subarctic gyre and global warming. Meanwhile, the contribution of the density decline to the TA increase is canceled out by that of the reduced vertical diffusive flux. We speculated that the winter TA increase is caused mainly by the accumulation of TA due to the weakened calcification by organisms during the winter. Key Points: Acidification of the western subarctic region has reduced the buffer capacity of this region faster than other open ocean time series sites Winter acidification occurs at a slower rate than annual mean acidification due to decline of DIC increase and TA increase Declined DIC increase is caused by the pycnocline depression and vertical diffusion flux decline due to gyre shrinkage and warming